Morphological and Molecular Characterization of Sumatra Disease of Clove in Central Java, Indonesia - Bambang Trianom; Triwidodo Arwiyanto; Tri Joko (Tropical Life Sciences Research, 2019)
A wilt clove disease has been reported recently that triggered a widespread devastation among clove plantings in Central Java, Indonesia. In the early stage, the younger leaves showed wilt suddenly, falling from the twig tip of branches in the crown, leaving the twig tip bare. However, older leaves may also turned brown and stay attached to the branches of infected plants. Several causative pathogens have been previously reported; including oomycetes, fungi, and bacteria. The aim of this research was to confirm the pathogen and to characterize the disease from clove plantings in the field. The research involved on morphological characterization, histology of infected plants, and molecular characterization of pathogens based on the endoglucanase (egl) gene. Bacterial ooze was observed on the tip of infected stems, and bacterial colonisation of xylem tissue was observed in the infected plants by cross-sections histology comparison. The pathogenic strain, designated KD1, was isolated from diseased tissue by dilution method and confirmed by Koch’s postulates. It showed hypersensitive reaction positive on tobacco and pathogenic to host plants. Partial egl sequence analysis revealed that the pathogen was closely related to Ralstonia syzygii subsp. syzygii (causative agent of Sumatra disease of clove) with sequence similarity of > 99%.